The influence of simultaneous handgrip and wrist force on forearm muscle activity. (April 2019) - Forman, Davis A.; Forman, Garrick N.; Robathan, Jason; Holmes, Michael W.R.
Abstract: The purpose of this study was to examine forearm muscle activity during simultaneous execution of dual motor tasks; hand-gripping and wrist forces. Surface electromyography was recorded from eight muscles of the upper-limb: flexor carpi radialis, flexor carpi ulnaris, flexor digitorum superficialis, extensor carpi radialis, extensor carpi ulnaris, extensor digitorum, biceps brachii and triceps brachii. Participants were seated with their forearm supported in a neutral position with an adjustable force transducer placed on either the palmar or dorsal side of the hand (for palmar/dorsal forces). Participants performed trials of simultaneous handgrip and wrist forces of various magnitudes, ranging in intensity from 0 to 40% of their maximal voluntary contraction. Trials lasted 5 s and force and electromyography data were assessed. The wrist flexors provided greatest contributions to tasks dominated by palmar forces but exhibited very low muscle activity in dorsal dominant tasks. Wrist extensors were active at moderate-to-high levels across nearly all conditions and demonstrated greater activity than the wrist flexors during handgrip-dominant tasks. These findings suggest that the wrist extensors provide the greatest contribution to wrist stiffness in complex motor tasks, and highlight the importance of investigating forearm muscle recruitment strategies under dual task parameters.